Resultados de coincidência para operadores multilineares múltiplo somantes - Rodríguez, Diana Marcela Serrano (2011)
In this work, we present some properties of the class of multiple summing multilinear operators. We summarize the theory with the aim of showing in details recent results such as coincidence results, inclusion results and results involving cotype.